Rehabilitasi Desain Bendung Tukuman Kali Dengkeng Cawas Kabupaten Klaten– Jawa Tengah - Adi Setyo Christanto; Aditya Yoga Kusuma; Abdul Kadir; Dwi Kurniani (Jurnal Karya Teknik Sipil, 2013)
Tukuman Weir is a weir of Dengkeng Cawas River, Klaten Regency, Central Java. This weir got a severe damage due to the excessive discharge in December 1989. This caused the people around the weir irrigated their field by free intake. The problems discussed in this paper are 1) the damage of the weir overflow, and 2) the damage of the tail water. The aim of the research is to maximize the flow of water into the irrigation network that the need of irrigation water can be met properly to increase the income of farmers each year. This research uses the latest data which then is processed by using hydrological analysis as the basic of the next planning. Watershed (DAS) of Dengkeng River is 101, 157 km2 in large, with three rain stations: Gantiwarno, Kemudo and Ngelo. The calculation of flood discharge plan uses several methods. The chosen discharge is the result of the calculation using HSS Gama I method with return period of 100 years, then continued with Qdesign=110 m3/sec. The large of the irrigation area of Tukuman weir is 150 hectares, with 0.22 m3/sec water need. From the result of the balance sheet analysis, the need of water irrigation is fulfilled, even it is a surplus. The rehabilitation concept is combining the fixed and barrage, but keeping the elevation of the old weir overflow. The redesign of the weir dimension with the fixed weir, the elevation height of the overflow is +102.02 m.dpl, rounded overflow with effective width of 7.75 m. While for the motion overflow, the overflow elevation is +99.7 m.dpl as planned, with 5 doors and effective width of each is 2.5 m. the length of the floor to the weir face is 10.5 m as planned, and the tail water of USBR type III is chosen. The cost of the weir rehabilitation is Rp. 3,241,000,000 with time estimation is 20 weeks. Based on the calculation, it is obtained that there is surplus on the water need that might be considered using it for other needs, for instance, enlarging the irrigation area or fulfilling drinking water needs.